(untitled) (International Journal of Scientific Trends, 2026)
This article analyzes issues of human interest and moral responsibility during the application of artificial intelligence technologies. It is highlighted that in modern society, artificial intelligence is being widely implemented in many fields such as medicine, education, economics, management, and information exchange, which, along with its positive potential, also raises complex ethical issues. The article interprets principles such as the priority of human interests, justice, transparency, accountability, privacy of personal data, digital equality, and security as the primary criteria for assessing artificial intelligence.